Analisis Penggunaan Alat Pembayaran Digital “Gopay” Terhadap Pengimplemetasiannya Dikalangan Driver dan Konsumen Gojek - anggraini, widya; Muhammad Irwan Padli Nasution; Sri Suci Ayu Sundari (JEBS (Journal of Economic and Business Student), 2023)
In the era of technological advances today, there are many products about digital payment instruments, Gopay is one of the many digital payment tools that are very widely used by many people, especially in Indonesia. PT. Gojek Indonesia issued a cashless payment instrument product in the form of Gopay with the aim of making it easier for consumers to be more effective and efficient in making transactions that are covered in an application called Gojek. Gojek itself is a smartphone digital application service to make it easier for many people to carry out activities. As well as for traveling, buying food, shopping, delivering goods, as well as to make transactions to purchase credit, electricity accounts, water accounts, and much more in the application.